2019
DOI: 10.7150/thno.29400
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Transfer from Bone Marrow Mesenchymal Stem Cells to Motor Neurons in Spinal Cord Injury Rats via Gap Junction

Abstract: Recent studies have demonstrated that bone marrow mesenchymal stem cells (BMSCs) protect the injured neurons of spinal cord injury (SCI) from apoptosis while the underlying mechanism of the protective effect of BMSCs remains unclear. In this study, we found the transfer of mitochondria from BMSCs to injured motor neurons and detected the functional improvement after transplanting. Methods: Primary rat BMSCs were co-cultured with oxygen-glucose deprivation (OGD) injured VSC4.1 motor neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
156
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(170 citation statements)
references
References 55 publications
3
156
0
Order By: Relevance
“…Accumulating evidence has shown that mitochondrial transfer occurs via TNTs, gap junctions, microvesicles, cell fusion and transfer of isolated mitochondria [132,[242][243][244][245]. So far, mitochondrial transfer from MSCs has demonstrated protective effects in lung injury, bronchial epithelial injury, allergic diseases, damaged cardiomyocytes, alkali-burnt corneal epithelial cells, kidney injury, ischemic damage, neurotoxicity, and spinal cord injury [132,[246][247][248][249][250][251][252][253]. Numerous studies have identified several signals including release of damaged mitochondria, mtDNA and mitochondrial products along with elevated ROS levels that trigger mitochondrial transfer from MSCs to the recipient cells [241].…”
Section: Mitochondrial Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that mitochondrial transfer occurs via TNTs, gap junctions, microvesicles, cell fusion and transfer of isolated mitochondria [132,[242][243][244][245]. So far, mitochondrial transfer from MSCs has demonstrated protective effects in lung injury, bronchial epithelial injury, allergic diseases, damaged cardiomyocytes, alkali-burnt corneal epithelial cells, kidney injury, ischemic damage, neurotoxicity, and spinal cord injury [132,[246][247][248][249][250][251][252][253]. Numerous studies have identified several signals including release of damaged mitochondria, mtDNA and mitochondrial products along with elevated ROS levels that trigger mitochondrial transfer from MSCs to the recipient cells [241].…”
Section: Mitochondrial Transfermentioning
confidence: 99%
“…Sinclair et al summarized different modes of intercellular communication and mitochondrial transfer by MSCs. Retinoic acid, a gap junction potentiator, greatly enhances the mitochondrial transfer efficiency from BM-MSCs to neurons, and this effect is partially abrogated by 18β glycyrrhetinic acid, which is a gap junction potentiator [253]. Inhibiting microtubule/TNTs, gap junction formation, or microvesicle endocytosis abrogates the transfer of cytoplasmic material from MSCs to epithelial cells [258].…”
Section: Mitochondrial Transfermentioning
confidence: 99%
“…The phosphorylation of RIP3 then leads to activation of its substrate MLKL, and the phosphorylated MLKL regards as the activation of MLKL (Wang et al, 2018b). We examined the protective effects of NSA in oxygen-glucose deprivation (OGD)induced cell damage assay that replicates the pathological condition of SCI in vitro through RIP3 and MLKL activation (Wang et al, 2018b;Li et al, 2019;. We also examined the protective effects and the therapeutic window of NSA in SCI-mice.…”
Section: Introductionmentioning
confidence: 99%
“…A 10-g weight (#WH160162; Convergence Technology Co., Ltd, Shenzhen, China) was dropped from a height of 50 mm into the exposed spinal cord and the impounder was left for 20 seconds before being withdrawn to produce a moderate contusion in the SCI group, as described in our previous study. 31 The 60 animals that underwent decompressive durotomy were anesthetized again 4 hours after the initial injury, and the segment was reexposed. A durotomy with a 4-mm diameter was performed using microscissors under a dissecting microscope.…”
Section: Animal Surgerymentioning
confidence: 99%